THE EXTENT PRINCIPALS EMPLOY THE ESSENTIAL PRACTICES IDENTIFIED BY PREVIOUS RESEARCH AND INTERPRETED BY THE RESEARCHER AS NECESSARY FOR STRONG INSTRUCTIONAL LEADERSHIP IN THE USE OF FORMATIVE ASSESSMENT BY TEACHERS - Privette, Cynthia S. (East Carolina University, 2015)
This study examined the extent principals employ the critical skills and practices identified by previous research and interpreted by the researcher, as necessary for effective instructional leadership in the use of formative assessment by teachers. As well, the study identified what principals perceived as necessary and challenging to instructional leadership in embedding formative assessment into the school culture. The research design for the study was a mixed-methods approach beginning with a quantitative evaluation as the primary method and continuing with a qualitative perspective to analyze the quantitative results. The quantitative portion of the study relied on a survey developed around the concept that a relationship existed between the essential practices necessary for principals to lead schools in the stages of the formative assessment process–implementation, utilization, and sustainability, and the four categories of principals’ instructional leadership responsibilities–curriculum, instruction, supervision, and evaluation. The qualitative piece consisted of open-ended questions to capture the overarching contextual conditions principals characterized as necessary and challenging to successfully execute the formative assessment process and establish themselves as leaders in formative assessment. The results of the study revealed that within all stages of the formative assessment process, the majority of principals somewhat, or to a small degree, performed the essential practices in the four categories and of instructional leadership and stages of formative assessment. The study also demonstrated that principals need professional development, clarity and established procedures related to the principals’ role. Additionally, principals are frustrated by a lack of staff, the number of initiatives imposed by district and state leadership, and with traditional views about teaching and learning. Results of the study support two major recommendations for research and practice. First, a comparative analysis on the extent principals use essential practices for instructional leadership between participating school districts, between school levels represented, and between principals with various years of experience will determine if a relationship exists. Secondly, more formal procedures consisting of established procedures, expectations, and training needs to take place before principals are adept at embedding the formative assessment process into the culture of the schools.
Keywords: principals; formative assessment practices; Educational evaluation; Educational leadership; School principals--Attitudes; Teacher-principal relationships